Research methods for education - Newby, Peter (Routledge, Taylor & Francis Group, 2014)
Written with the novice educational researcher in mind, this book is designed to help students produce good quality, valid and valuable research. The text is written in an engaging style and adopts a mixed-methods approach. It also features guidance on analytical procedures that require more advanced tools--Resumé vydavatele
Terminologický slovník
Keywords: pedagogický výzkum -- metodologie; výchova a vzdělávání; kurikulum; educational research -- methodology; education; curriculum; učebnice; textbooks